Quitting smoking and willingness to pay for cessation in Panama - Víctor H Herrera-Ballesteros; Julio Zúñiga; Ilais Moreno; Beatriz Gómez; Reina Roa-Rodríguez (Instituto Nacional de Salud Pública, 2017)
Objective. To characterize the desire for cessation and willingness to pay for abandonment therapy. Materials and methods. The data source is the Global Adult Tobacco Survey (GATS). Cessation and willingness to pay were characterized by sociodemographic (SD) and socioeconomic (SE) variables. Logistic regressions were performed to estimate associations. Results. A greater desire for cessation was observed in variables: women, education, non-governmental and inactive employees, rural areas, occasional smokers and middle income, and greater willingness to pay, in: education, over 60 years old, non-governmental, self-employed, urban area, occasional smokers and low median income. Con- clusions. There is a high relation between the desire for abandonment, and willingness to pay with SD and SE variables. Cessation therapies can be applied in work centers, and require a change of focus in the intervention.